THE IMPACT OF COVID-19 PANDEMIC ON THE CAPITAL EXPENDITURES OF PROVINCES IN INDONESIA - Jouzar Farouq Ishak (Jurnal Ilmiah Ekonomi Bisnis, 2022)
This study aims to compare the capital expenditure of the province of Indonesia between pre and post Covid-19 in. The data type used was secondary data for 2019 and 2020 which was obtained from the official website of the Directorate General of Regional Fiscal Balance. The paired sample t-test was applied to test the hypothesis. This study concludes that the Covid-19 pandemic has an effect on capital expenditure of the provinces in Indonesia. The negative impact of the Covid-19 pandemic on capital expenditure by refocusing and reallocation budgeting where in terms of capital expenditure experiencing a slowdown due to the budget being used for priorities aimed at health, social assistance, and economic recovery.  The government did not stop activities and capital expenditures during the Covid-19 pandemic where in a crisis, the government had to intervene primarily for health spending. The government cannot delay until it has sufficient state revenues. Regional governments continue efforts to improve economic recovery while consistently prioritizing fundamental sectors in handling Covid-19 as the key to economic recovery. Utilization of this capital expenditure budget should be more focused on supporting priority programs, promoting the efficiency of the basic needs of the community and keeping the implementation of activities and capital expenditure budgets based on results.